Work Stress, Role Conflict, and Compensation Inequity as Antecedents of Turnover Intention: Evidence from Private Hospital Employees in Central Java - Fatwa Zuhaena (JURNAL ILMIAH EDUNOMIKA, 2020)
The global healthcare industry continues to face a pressing human resource challenge: high employee turnover. This study examines the influence of work stress, role conflict, and compensation inequity on turnover intention among employees of private hospitals in Banyumas Regency and adjacent districts, Central Java. Grounded in Conservation of Resources (COR) Theory (Hobfoll, 1989) and Equity Theory (Adams, 1963), three hypotheses were tested using PLS-SEM with a sample of 145 respondents from five accredited private hospitals. Results demonstrate that work stress (β = 0.312, p < 0.001), role conflict (β = 0.341, p < 0.001), and compensation inequity (β = 0.358, p < 0.001) each significantly and positively affect turnover intention, with compensation inequity exerting the strongest effect. The three predictors jointly explain 61.4% of turnover intention variance (R² = 0.614; Q² = 0.388). These findings provide theoretically grounded, empirically supported recommendations for hospital administrators seeking effective retention strategies in Central Java's private healthcare sector. Keywords: work stress; role conflict; compensation inequity; turnover intention; private hospital; COR theory; equity theory; PLS-SEM